2013
DOI: 10.2217/fon.13.33
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Treatment Response in Hepatocellular Carcinoma: A Review of the Literature

Abstract: Hepatocellular carcinoma (HCC) has a high incidence all over the world. Even if the primary end point of treatment of HCC is survival, radiological response could be a surrogate end point of survival, and could have a key role in clinical management. Since 1950 several radiological response criteria have been applied; however, it was not until 2000 that specific criteria for HCC were introduced by the European Association for the Study of the Liver (EASL), and these were then standardized in 2010 with the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…To overcome these limitations, the EASL and mRECIST criteria have been suggested to be a better way of assessing tumor response in HCC patients. Several studies, recently reviewed [ 28 ], demonstrated their superiority over conventional criteria. The evaluation of tumour viability, represents the most relevant change in EASL/mRECIST criteria compared to traditional WHO/RECIST.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, the EASL and mRECIST criteria have been suggested to be a better way of assessing tumor response in HCC patients. Several studies, recently reviewed [ 28 ], demonstrated their superiority over conventional criteria. The evaluation of tumour viability, represents the most relevant change in EASL/mRECIST criteria compared to traditional WHO/RECIST.…”
Section: Discussionmentioning
confidence: 99%
“…[16] So, complete response is a relevant surrogate end-point that should be planned and carefully assessed by multiphasic CT or MR scan in all patients who undergo RFA. [8], [19].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, liver cancer patients are already in an advanced disease stage upon diagnosis, which limited the efficacy of radiotherapy and chemotherapy [5,6]. Although rapid development and wide application of imaging technology, pathology and molecular genetics have benefited HCC patients, death rates are still increasing rapidly for liver cancers [7][8][9][10][11]. Therefore, progressive fights against cancers need consistent clinical and basic research to improve treatment outcome and benefit survival.…”
Section: Introductionsmentioning
confidence: 99%